COMBINATION OF LEPTIN ANALOG AND SALBUTAMOL: TREATMENT APPROACH FOR OBESITY-INDUCED ASTHMA - ARUN K SONI; SHRIKALP S DESHPANDE (Asian Journal of Pharmaceutical and Clinical Research, 2019)
Objective: The objective of the study was to investigate the effect of leptin analog and salbutamol in obese asthmatic mice. Methods: Obese asthmatic condition was induced by administration of hypercaloric diet for 8 weeks followed by ovalbumin-aluminum hydroxide. The animals were treated with leptin analog (0.4 mg/kg, i.p. for 14 days) and salbutamol (2 mg/kg, PO for 14 days). Biochemical parameters such as serum leptin, ghrelin, and tumor necrosis factor-α and physical parameters such as tidal volume and airflow rate were estimated to confirm the state of asthma and obesity, respectively. Results: Elevated serum leptin and ghrelin were associated with leptin resistance in obese asthmatic mice. It was found that a significant increase in serum leptin level with animal treated with leptin analog and salbutamol when compared to animals treated with leptin analog alone. The result of respiratory parameters and serum parameters also improved with the combination of leptin analog and salbutamol. From our study, we found that salbutamol potentiates the effect of leptin analog in obese asthmatic condition. Conclusion: Leptin analog and salbutamol are an alternative treatment approach to treat the obese asthmatic condition.